2020
DOI: 10.1371/journal.pone.0241556
|View full text |Cite
|
Sign up to set email alerts
|

Sex disparities in dialysis initiation, access to waitlist, transplantation and transplant outcome in German patients with renal disease—A population based analysis

Abstract: Background Renal transplantation access and outcome differ between men and women, but no analysis has considered all transition phases and transplant outcome using the same data set. We analyzed sex disparities in all phases of patients’ clinical path (progression to dialysis, waitlisting, transplantation, graft failure/death). Methods In a population based approach using health insurance data (2005–2013) we examined patients’ risk of changing from one phase to another applying Cox Proportional Hazards model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 47 publications
1
16
1
Order By: Relevance
“…Our analysis follows a recently articulated request ( 16 ) to start focusing on non-North American cohorts in examining how sex and gender affect transplantation and compared them with the US. In accordance with previous data from the US ( 1 – 8 , 24 , 33 , 40 ), Canada ( 41 ), France ( 42 ), Australia ( 43 ) and Germany ( 44 ), in our analysis predominantly older women have lower access to kidney transplantation than men. Knowing the development in the US and Austria over the last four decades is informative, and this development renders it likely that gender disparity is the root cause of the observed sex differences in kidney transplantation.…”
Section: Discussionsupporting
confidence: 92%
“…Our analysis follows a recently articulated request ( 16 ) to start focusing on non-North American cohorts in examining how sex and gender affect transplantation and compared them with the US. In accordance with previous data from the US ( 1 – 8 , 24 , 33 , 40 ), Canada ( 41 ), France ( 42 ), Australia ( 43 ) and Germany ( 44 ), in our analysis predominantly older women have lower access to kidney transplantation than men. Knowing the development in the US and Austria over the last four decades is informative, and this development renders it likely that gender disparity is the root cause of the observed sex differences in kidney transplantation.…”
Section: Discussionsupporting
confidence: 92%
“…There are gender and sex differences that negatively affect women with KF from the initial diagnosis through access to a substitute renal treatment [ 13 , 14 ], including renal transplant [ 15 ]. Some studies have shown lower QoL among women in HD [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in the United States, it has been shown that women in the general population are less aware of their CKD, both in early and late stages, 30 that men are better prepared with arteriovenous fistulas at dialysis initiation, 31 and that women on dialysis have lower chances to enter wait-lists for kidney transplantation. 32 All of these reports indicate better CKD diagnosis and treatment for men.…”
Section: Discussionmentioning
confidence: 99%